2016
DOI: 10.1039/c5cp06836c
|View full text |Cite
|
Sign up to set email alerts
|

A mixed iron–manganese based pyrophosphate cathode, Na2Fe0.5Mn0.5P2O7, for rechargeable sodium ion batteries

Abstract: The development of secondary batteries based on abundant and cheap elements is vital. Among various alternatives to conventional lithium-ion batteries, sodium-ion batteries (SIBs) are promising due to the abundant resources and low cost of sodium. While there are many challenges associated with the SIB system, cathode is an important factor in determining the electrochemical performance of this battery system. Accordingly, ongoing research in the field of SIBs is inclined towards the development of safe, cost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 30 publications
(43 reference statements)
0
30
0
Order By: Relevance
“…c) Cyclic voltammetry (CV) data for Na 2 Fe 0.5 Mn 0.5 P 2 O 7 , Na 2 MnP 2 O 7 and Na 2 FeP 2 O 7 . Reproduced with permission 71. Copyright 2016, Royal Society of Chemistry.…”
Section: Recent Advances In Polyanion‐type Electrode Materials For Namentioning
confidence: 99%
See 1 more Smart Citation
“…c) Cyclic voltammetry (CV) data for Na 2 Fe 0.5 Mn 0.5 P 2 O 7 , Na 2 MnP 2 O 7 and Na 2 FeP 2 O 7 . Reproduced with permission 71. Copyright 2016, Royal Society of Chemistry.…”
Section: Recent Advances In Polyanion‐type Electrode Materials For Namentioning
confidence: 99%
“…However, Na 2 MnP 2 O 7 has been shown to have an inferior rate capability due to the intrinsic lower electronic conductivity of Mn 69. Therefore, a mixed transition metal pyrophosphate material, Na 2 Fe 0.5 Mn 0.5 P 2 O 7 , was synthesized by substituting some Mn with Fe 71. Ex situ XRD and cyclic voltammetry (CV) analyses indicated that Na 2 Fe 0.5 Mn 0.5 P 2 O 7 is a single‐phase reaction due to different Na site occupancy as compared to the biphasic reaction of Na 2 FeP 2 O 7 and Na 2 MnP 2 O 7 .…”
Section: Recent Advances In Polyanion‐type Electrode Materials For Namentioning
confidence: 99%
“…For example, carbon nanotubes decorated Na 2 FeP 2 O 7 was demonstrated to have a high rate capability at 20 C rate,166 and can work well in inorganic ionic liquid 167, 168. Due to the higher electrochemically active Mn 3+ /Mn 2+ redox potential, Manganese substitution were also employed to raise the average redox potential up to 3.2 V 169, 170. Ex situ XRD and CV analyses indicated that Na 2 Fe 0.5 Mn 0.5 P 2 O 7 underwent a single phase reaction rather than a biphasic reaction due to different Na coordination environment and different Na sites occupancy 169.…”
Section: Pyrophosphate Materials For Na Storagementioning
confidence: 99%
“…Due to the higher electrochemically active Mn 3+ /Mn 2+ redox potential, Manganese substitution were also employed to raise the average redox potential up to 3.2 V 169, 170. Ex situ XRD and CV analyses indicated that Na 2 Fe 0.5 Mn 0.5 P 2 O 7 underwent a single phase reaction rather than a biphasic reaction due to different Na coordination environment and different Na sites occupancy 169. Recently, off‐stoichiometric iron‐based pyrophosphate, named Na 2–x Fe 1+x/2 P 2 O 7 , were reported To have similar structure and charge/discharge plateaus with Na 2 FeP 2 O 7 , but higher reversible capacity (114 mAh g –1 ) and better cyclability exceeding 3000 cycles in ionic liquid electrolyte 171, 172, 173, 174, 175…”
Section: Pyrophosphate Materials For Na Storagementioning
confidence: 99%
“…[154] Mixed-cation pyrophosphates have been also developed with the aim of obtaining enhanced electrochemical performance, especially in cycling stability. [155,156] …”
Section: Pyrophosphatesmentioning
confidence: 99%